Nonlinearity of optoacoustic signals and a new contrast mechanism for imaging - Jaber Malekzadeh-Najafabadi; Jaya Prakash; Daniel Razansky; Jorge Ripoll; Vipul Gujrati; Vasilis Ntziachristos (Light: Science & Applications)
Abstract Optoacoustic signals behave nonlinearly at light fluences above a few mJ/cm2, which may affect the interpretation and quantification of measurements. It has been proposed that optoacoustic nonlinearity arises from the heat-induced formation of nanobubbles or changes in local thermo-physical parameters. However, such explanations are only valid at much higher fluences than typically used in biomedical optoacoustic imaging (> 20 mJ/cm2) or in the presence of materials with high absorption coefficients such as gold nanoparticles. We propose herein that electromagnetic permittivity changes in response to photon absorption are major source of optoacoustic signal nonlinearity at low fluences. We provide theoretical and experimental evidence that supports this postulation and show that optoacoustic pressure responses due to permittivity changes, which are function of thermally excited third-order nonlinear susceptibility, can explain the nonlinear behavior of the optoacoustic signal. Since different materials exhibit different thermally excited third-order nonlinear susceptibility, this property could function as a new contrast mechanism that can identify the sensitivity of a substance’s dielectric constant to photon-induced temperature changes. Consequently, we propose an imaging method based on nonlinear optoacoustic signals that exploits this newly identified contrast mechanism. These findings may have far-reaching implications for improving the accuracy of optoacoustics and utilizing the proposed new contrast mechanism would advance our understanding of cellular and tissue functionality.